The role of organisational culture in adopting digital platforms in South African banks - Barnes, LeRoy Curtis (University of the Witwatersrand, Johannesburg, 2024)
The advancement and pervasiveness of digital technologies are causing significant disruptions in the banking industry’s market definitions, operations, and business models, resulting in a surge in digital transformation in the banking sector in the past decade. This research contributes to the existing literature by evaluating the organisational culture of South African banks and examining how it promotes or hinders the adoption of digital platforms. This research explored how organisational culture influences the adoption of digital platforms within South African banking institutions. Twelve attributes were used as variables to describe digital organisational culture alongside the technology-organisation-environment (TOE) framework. The study uses a quantitative approach to validate theory and examine variable interrelations. The study collected responses from 127 South African banking sector employees using non-probability convenience sampling. A Likert scale questionnaire with 17 questions captured respondents’ feedback on digital organisational culture and digital platform adoption. Reliability and descriptive statistical analysis, Shapiro-Wilk test Factor analysis, Regression analysis, Correlation analysis (Spearman’s Rho), Mann-Whitney U test, and Kruskal-Wallis test were employed to analyse the data. The study found that digital organisational culture positively influences digital platform adoption in the banking sector. The factors within digital organisational culture that have a significant influence are cross-functional teams, digital skills, and start-up mentality. However, mutual decision-making was found to have a significant negative influence on adoption. The Mann-Whitney U test suggests no significant differences in digital platform adoption between traditional and digital banks. The test also suggests no significant differences in the perceptions of digital culture factors between traditional and digital banks, except for failure culture. The Kruskal-Wallis test results indicate no significant differences in the iii distribution of most variables tested across organisational roles, except for cross- functional teams. The study underscores the crucial importance of collaborative, agile, and innovative cultures within banking organisations, as observed through the significant roles of cross-functional teams and the positive correlation of start-up mentality. The study also highlights the need for ongoing investment in digital skills development and the strategic repositioning of IT departments to support digital transformation objectives effectively. Moreover, the strong positive correlation between customer integration and digital platform adoption emphasises the crucial role of customer-centric approaches in the digital transformation process.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg 2024
Keywords: Banking, cross-functional teams; Digital culture; Digital organisational culture; Digital platform adoption; Digital transformation; Organisational culture; UCTD; SDG-8: Decent work and economic growth